Symbiosis between the Lean Manufacturing concept and progressive informatization - Pawłyszyn, Irena (Symbioza koncepcji Lean Manufacturing z postępującą informatyzacją, 2019)
The purpose of this article is to present a number of IT systems and technologies that support the solutions of the Lean Manufacturing (LM) concept. The enterprises’ pursuit to improve the efficiency of their business activities caused a revolution in the use of information systems. Contemporary organizations wanting to occupy leading positions on the market cannot do it without appropriate IT solutions that will facilitate the analysis of business processes and making the right economic decisions. Nevertheless, each company is a separate “living organism” that should be treated individually, and the information technology used should become a way to solve specific problems and support the implementation of certain improvements. This article presents a number of IT solutions that are or may become in the near future support for Lean initiatives
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 49-61
Keywords: lean manufacturing; informatization; IT systems and technologies; informatyzacja; systemy i technologie informatyczne